Pengaruh Modal, Tenaga Kerja, dan Bahan Baku Terhadap Pendapatan Industri Mebel Kayu di Kota Banjarmasin (Studi Kasus Kelurahan Alalak Tengah Kecamatan Banjarmasin Utara) - Jahrani, Muhammad (PPJP ULM, 2018)
This study aimed to (1) analyze the effect of capital, labor, and raw materialon the wooden furniture industry; (2) to determine which factors dominantly, in fact,the income of the wooden furniture industry. The scope of this study took the case study area in Kelurahan Alalak Tengah,Kecamatan Banjarmasin Utara, Kota Banjarmasin. The data sources are primarydata obtained through interviews and questionnaires to be processed using multipleregression analyses, tested through f best (simultaneously), and t-test (partially). The resultsnofmthisbstudynindicate that the capital, labor, and raw materialsindividually (partially) and simultaneously have a positive and significant effect onthe income of the wood furniture industry. The most dominant factor affecting theincome of the wooden furniture industry is raw material.